2021
DOI: 10.3390/app11219807
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically-Induced Pressure Generation in Magnetorheological Fluids under the Influence of Magnetic Fields

Abstract: This study aims to observe the magnitude of the Magnetorheological Fluids (MRFs) pressure due to the application of a magnetic field. This was accomplished by placing the MRFs in a U-shaped tube, then applying a magnetic field generated by a magnetic coil. A finite element simulation for the magnetic field was carried out to estimate the magnetic field strength generated by the coil variable to the current input given in the simulated apparatus. Changes in MRFs pressure were recorded using a data logger to bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…From the comparison of the application of current strength in Table 2, it is shown that the magnitude of the current applied to the MRF correlates with the resulting liquid pressure, as has been disclosed in previous studies [33]. In addition to the strong electric current, the amount of pressure is also influenced by the accumulation of magnetic particles on one side of the channel.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…From the comparison of the application of current strength in Table 2, it is shown that the magnitude of the current applied to the MRF correlates with the resulting liquid pressure, as has been disclosed in previous studies [33]. In addition to the strong electric current, the amount of pressure is also influenced by the accumulation of magnetic particles on one side of the channel.…”
Section: Discussionsupporting
confidence: 60%
“…In previous studies, observations have been made with regard to changes in the magnitude of MRF pressure as a result of variations in the application of magnetic field strength to MRF [33]. From these observations, it can be seen that the phenomenon of a change in pressure strength associated with a change in the magnitude of magnetic field strength, which is represented in the form of a robust electric current applied to a magnetic coil, exists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because as the eccentricity increases, the siz of the converging wedge inlet of the magnetic fluid lubricant film increases and the siz of the outlet decreases, accumulating more and more magnetic fluid near the outlet of th converging wedge and increasing pressure; the size of the diverging wedge inlet de creases and the size of the outlet increases, with less and less magnetic fluid near the di verging wedge inlet and decreasing pressure. Thus, the magnetic fluid lubricating oil film has a strong wedge effect, and the oil film carrying capacity is increased, leaving the jour nal in a relatively balanced position [31]. Figure 10 gives the oil film temperature distribution of magnetic fluid bearings with different eccentricity.…”
Section: Flow Field Analysis Of Magneto-fluid Lubricated Bearingsmentioning
confidence: 99%
“…In addition, a study of the magnetic flux density along the axis of symmetry of the bladder above the face of the electromagnet is provided. In the article [23], FEM was used to correlate simulation data with experimental measurements of the real object to then perform a study of the magnetic flux density inside the core of the coil containing the MRF. In the aforementioned papers, FEM simulations have been used to represent the magnetic field distribution of the proposed gripper solutions or to study the behaviour of the MRF.…”
Section: Introductionmentioning
confidence: 99%